Designing physical activity interventions for women aged 50+: a qualitative study of participant perspectives - Geraldine Wallbank; Abby Haynes; Anne Tiedemann; Catherine Sherrington; Anne C. Grunseit (BMC, 2022)
Abstract Background The Active Women over 50 trial tested a scalable program for increasing physical activity among women aged 50+. The program included information, activity tracker and email support. This study sought to describe the participant perspectives of the Active Women over 50 program and considerations for designing physical activity interventions for this demographic. Methods Women who completed the Active Women over 50 trial were purposively recruited for maximum variation in age, employment, carer responsibility, medical conditions and physical activity. Individual semi-structured interviews explored their perspectives on physical activity, Active Women over 50 program components and suggestions for future iterations. Data were thematically analysed. Results Participants' capacity to be physically active was shaped by an interplay of factors. Our analysis generated four main themes relating to physical activity in general and to the program: Age and gender matters, Physical activity is social, Strategising for physical activity and the Self-responsibility discourse. At this midlife stage, physical activity participation was challenged by personal, life-stage and cultural factors, alongside a tension of the self-responsibility discourse which also impacted the program experience. Social factors and finding a suitable strategy for motivation were deemed integral aspects of being active. Future programs could consider facilitation of social networks and accountability, life-stage health information and positive framing to support self-responsibility. Conclusion A range of strategies is key to supporting women over 50 to be more physically active due to the variety of circumstances and levels of agency experienced. We offer suggestions that do not need to be resource intensive but could be incorporated into a scaled program.